Rice Responses To A Short-Duration Green Manure .2. N Recovery And Utilization - Morris, R.A.; Furoc, R.E.; Dizon, M.A. (Wiley, 1986)
Recent research demonstrated that fast‐growing tropical legumes [mungbean, Vigna radiata(L.) Wilczek and cowpea, V. unguiculata(L.) Walp.], when used as a green manure for lowland rice (Oryza sativaL.), can increase grain yield by 2 Mg ha−1, and that supplemental inorganic applications increase yield further. To guide research on the combined use of inorganic and green manure N, apparent N recovery (kg N uptake kg−1N applied) and N utilization (kg grain kg 1N uptake) were determined in three experiments. The experiments were conducted on a fine mixed isohyperthermic Aeric Tropaqualf in the Philippines during the 1983 and 1984 wet seasons. In two experiments, factorial combinations of inorganic N (0 and 80 kg N ha 1) and green manure growth duration (20, 30, and 40 days in the first year; 25,35, and 45 days in the second year), were tested. Apparent N recoveries from inorganic fertilizer and green manure were 49% in 1983 and 41% in 1984. At N levels < 51 kg N ha−1, inorganic N utilization was inferior to green manure N utilization in 1983 but similar in 1984. In the third experiment, mungbean was planted at 300 000 and 600 000 plants ha−1and grown for 20, 30, and 40 days before incorporation. Inorganic N (80 kg N ha−1) was applied to plots that were fallow during the green manure growth period. Apparent N recovery from both sources was 33%. Utilization of N from 80 kg inorganic N ha−1was slightly more efficient than from an equivalent quantity of green manure N. Although differences were noted, the experiments suggest that apparent recovery and utilization of N from short‐duration green manures are similar to those from inorganic N fertilizers. Research is required to determine how efficiency from the combined use of both N sources can be maximized.